Possibilities of shaping the historical urban space in Ciechanow based on the city map and registry from 1851 - Kęsik, Grzegorz (Przestrzenny wymiar badań dziedzictwa kulturowego: Studia z Geografii Politycznej i Historycznej 2020. T. 9-10, 2021)
The chapter concerns the problems of shaping historical urban space based on the archival city map and registry of Ciechanow from 1851, by the famous Mazovian surveyor, Joachim Łuszczewski. City map, made on a scale of 1:1 500, discovered in 1989 in the State Archives in St. Petersburg, in 2017 was “imported” to Poland in the form of a large graphic file. The only polish expemlary of this map (originally map was made in triplicate) was destroyed in September 1939 during German air raids on Warsaw. In addition, in 2003 in the State Archives in Plock, was found a registry of the seats of the city of Ciechanów (made by the same surveyor), which document turned out to be fully compatible with the said city map. These archives (plan and registry) are a very valuable find on the scale of Mazovia where, apart from Warsaw and Plock, very little of such accurate and complete large-scale nineteenth-century cartographic material has survived. The city map and registry from 1851 provide an opportunity to re-restore (using information boards, archaeological research or big infrastructure investments) some of the old places in the contemporary historical space of Ciechanow.